Stylistic Analysis in a Collection of Poetry Tears of Batu by Fakhrunnas Ma Jabbar - Suci Eliani; Sudirman Shomary (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Literature is a work of art that produces beautiful creative works that can be poured or created by humans. The beauty of language is easily seen in literary works, especially by using stylistic analysis. Therefore, the author is interested in conducting a research entitled "Analysis of Stylistics in a Collection of Poetry Tears of Batu by Fakhrunnas Ma Jabbar". The problems in this study (1) how is the stylistic analysis of lexical elements in the poem Airmata Batu by Fakhrunnas Ma Jabbar? (2) how is the stylistic analysis of rhetorical means in the poem Airmata Batu by Fakhrunnas Ma Jabbar?. This study aims to find and analyze the lexical elements and rhetorical means contained in the poem Airmata Batu by Fakhrunnas Ma Jabbar. The theory used in this study is the theory of Nurgiantoro (2014) about stylistics, and several other supporting theories. The data of this research was taken from the collection of poetry Airmata Batu by Fakhrunnas Ma Jabbar. The method used in this research is descriptive method. The approach used in this research is a qualitative approach. This type of research is library research. Data collection techniques using hermeneutic techniques. The data analysis technique is that the data that has been obtained are grouped and presented, the grouped data is processed using the listed theories, text analysis, data interpretation, and concludes the data. The results of this study are as follows. First, the lexical elements contained in the poem Airmata batu are 7 data, the sound aspect is 7 data, and the meaning aspect is 7 data. Second, the means of rhetorical figurative language in simile comparisons contains 3 data, metaphor, 6 data, personification 17 data, allegory 2 data, figurative language linking metomini the author cannot find it, synecdoche 5 data. Rhetoric means visual imagery 5 data, auditory imagery 8 data, motion imagery 6 data, tactile imagery 4 data and olfactory imagery 4 data.